PENGARUH PENGGUNAAN QR CODE DALAM PEMESANAN MENU TERHADAP KEPUASAN KONSUMEN DI PORCH CAFFE - Putri Siti Alia Miranti; Fauzia Agustine; Ria Fitriani; Tina Azzani; Mulyana Jihad (Bajang Institute, 2025)
This study aims to determine the effect of QR code usage in ordering menus on consumer satisfaction at Porch Caffe. This study uses a quantitative method with a descriptive approach. Respondents in this study were Porch Caffe consumers who had used QR codes in ordering. The sampling technique used accidental sampling technique with 105 respondents. Data collection techniques used observation, questionnaires, and documentation. The data obtained were analyzed using simple linear regression, t-test, and coefficient of determination. The results showed that the use of QR codes had a significant effect on consumer satisfaction with a t count value (3.178) > t table (1.927). The coefficient of determination of 8.9% indicates that the variable of QR code usage only has a small effect on consumer satisfaction, the rest is influenced by other variables outside this study.